Management of idiopathic alveolar bone necrosis associated with oroantral fistula after upper left first molar extraction - Ni Putu Mira Sumarta (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Complications such as alveolar osteonecrosis and oroantral fistula can occure in maxillary molar extraction. The management of such complication is done by treating to treat any persisting maxillary sinusitis if present, prevent further antral contamination, wound bed preparation, and oroantral fistula closure with appropriate method. Purpose: This case report presents a treatment stage of an idiopathic upper alveolar bone necrosis and oroantral fistula that occurred 4 months after left upper first molar extraction. Case: A case of an idiopathic upper alveolar bone necrosis associated with oroantral fistula that occurred 4 months after left upper first molar extraction is presented. Patient suffered from pain and swelling at left upper jaw since 2 month before admission. There was a history of complicated tooth extraction 4 months earlier. Patient also complained pus and blood discharge from post extraction socket. Patient occasionally choked when drinking and fluids escaped through the nostril. There was a diffuse swelling in the left maxillary region; there was no hyperemia, with soft consistency and no pain on palpation. In the 26, 27 region there was a